2022
DOI: 10.1021/acsnano.2c00265
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructure Engineering Strategies of Cathode Materials for Room-Temperature Na–S Batteries

Abstract: Room-temperature sodium−sulfur (RT Na−S) batteries are considered to be a competitive electrochemical energy storage system, due to their advantages in abundant natural reserves, inexpensive materials, and superb theoretical energy density. Nevertheless, RT Na−S batteries suffer from a series of critical challenges, especially on the S cathode side, including the insulating nature of S and its discharge products, volumetric fluctuation of S species during the (de)sodiation process, shuttle effect of soluble so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 160 publications
0
29
0
Order By: Relevance
“…Therefore, next-generation rechargeable Na–S batteries hold significant promise for large-scale energy storage systems. 7–9…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, next-generation rechargeable Na–S batteries hold significant promise for large-scale energy storage systems. 7–9…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, next-generation rechargeable Na-S batteries hold significant promise for large-scale energy storage systems. [7][8][9] Currently, the development of Na-S batteries greatly lags behind the mature Li-S batteries and is still in the preliminary stage. The study of Na-S batteries originates from the 1960s, and its operating temperature has been gradually lowered from high-temperature (300-350 °C), 10 to intermediate-temperature (120-300 °C), 11 and room-temperature (RT, 25-35 °C) 12 which is much safer and could achieve higher energy density.…”
Section: Introductionmentioning
confidence: 99%
“…The large surface area alleviates the dissolution of NaPS intermediates via chemisorption. 12 CoS 2 /C showed a narrow pore size distribution in the range of 0.8–4 nm, suggesting the co-existence of micro- and mesopores. The high content of sulfur encapsulated in the micro- and mesoporous CoS 2 /C had high electrical activity resulting from the close contact between Na ions and electrons.…”
mentioning
confidence: 98%
“…11 It is reported that single-atom Co and Co-based sulfides embedded in a carbon matrix derived from the MOF precursors are efficient hosts in RT Na–S battery cathodes. 12 Xiao and co-authors synthesized a polydopamine-coated Co-MOF derived mesoporous CoS 2 /NC cathode with excellent performance. 13 CoS 2 has been applied as a catalyst to weaken the S–S bond and promote the formation of insoluble short-chain polysulfides.…”
mentioning
confidence: 99%
“…However, Li-S is not the only aprotic sulfur-based battery chemistry currently in the spotlight in fundamental research worldwide: also Na-S, K-S, Mg-S, Ca-S, and Al-S battery chemistries are currently challenging the battery research field. ,,,,, To shed some light on this, the same comparative analysis outlined above for the Li-S case can be drawn also in these cases, thus highlighting the comparative merits of each battery chemistry. In Figure , the performance features and energy costs per active material mass are compared to the Li-ion and Li-S benchmarks, as well as the maximum volume variation suffered simultaneously by both active materials between charge/​discharge.…”
mentioning
confidence: 99%